The effectiveness of detection and prosecution of cybercrime threats against companies in South Africa - Naidoo, Shanine (niversity of the Witwatersrand, Johannesburg, 2023)
The rise of digital technology has brought about many benefits to modern society. However, this advancement has also led to an increase in cybercrime activities, which has become a significant threat to individuals and organizations worldwide. In South Africa, cybercrime attacks against companies have become increasingly rampant, posing significant risks to their operations and even their existence. As a result, there is a growing concern about the effectiveness of the measures put in place to detect and prosecute cybercrime threats against companies. The purpose of this report is to investigate the efficiency of detecting and prosecuting cybercrime attacks against South African companies. While the term "cybercrime" encompasses a broad range of activities, this research will focus primarily on evaluating cybercrime threats that specifically target companies and their cybersecurity. The reason for this is that such attacks can have dire consequences on companies' operations and existence, ranging from financial losses to reputational damage. To achieve this objective, the study will pursue a twofold approach. Firstly, it will evaluate the effectiveness of South Africa's legislation in detecting and prosecuting cybercrime threats against companies. This includes a comprehensive examination of the legal frameworks and policies currently in place to combat cybercrime activities in the commercial sphere. Secondly, it will evaluate whether companies can rely on law enforcement agencies in South Africa to provide adequate protection against such threats. This will involve a critical analysis of the capacity and capability of law enforcement agencies to respond to cybercrime attacks against companies. The findings of this report will contribute significantly to the understanding of the effectiveness of detecting and prosecuting cybercrime attacks against South African companies. The recommendations made will provide valuable insights into how to improve the detection and prosecution of cybercrime threats in the commercial sphere. This study will be beneficial to policymakers, law enforcement agencies, and companies operating in South Africa, as it will help to enhance their understanding of the threats posed by cybercrime and the measures needed to mitigate them
A research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2023
Keywords: Digital technology; Cybercrime attacks; South African companies; Cybersecurity; Effectiveness of detection; UCTD; SDG-9: Industry, innovation and infrastructure